Umur dan Kecelakaan Kerja pada Anak Buah Kapal: Penelitian Cross-sectional - Ferika Sumerah; Oksfriani Jufri Sumampouw; Nova Hellen Kapantow (Universitas Sam Ratulangi, 2024)
Background: The Coastal Fisheries Port and Fish Auction Place, located in Tumumpa Dua are one of the main factors supporting fisheries businesses, especially capture fisheries and fishing boat bases, unloading fish, conducting fish auctions and fish marketing. The crew ship member is one of the workers who works at the Tumumpa Coastal Fisheries Port. The purpose of this study is to measure the correlation between age and the incidence of work accidents in crew ship members at Tumumpa Beach Fisheries Port, Manado City. Methode: This is an observational research with a cross sectional approach. This research is located at the Tumumpa Beach Fisheries Port, Manado City in June-July 2023. The respondents of this study were 242 crew members. The variables for this study are age and work accidents. The instrument used was a questionnaire. Data analysis carried out bivariately. Results: The results showed that among the 232 respondents who experienced the most work accidents distributed at the age of ≥ 30 years old, as many as 186 respondents (80%), while of the 10 respondents who had never experienced a work accident, the most were also found at the age of ≥ 30 years as many as 7 respondents (70%). The results of the Chi Squared test showed a significance value of 0.428 (> 0.05) which means that there was no correlation between age and the incidence of work accidents in crew ship members. Conclusion: It can be concluded that there is no correlation between age and the incidence of work accidents in crew ship members at Tumumpa Beach Fisheries Port, Manado City.